Factors influencing healthcare seeking in patients with dengue: Systematic review. Issue 1 (27th October 2021) - Ng, Tze Chang; Teo, Chin Hai; Toh, Jia Yong; Dunn, Adam G.; Ng, Chirk Jenn; Ang, Tan Fong; Abdullah, Adina; Syed, Ayeshah; Lim, Hooi Min; Yin, Kathleen; Liew, Chee Sun
Abstract: Objective: Delays in seeking healthcare for dengue are associated with poor health outcomes. Despite this, the factors influencing such delays remain unclear, rendering interventions to improve healthcare seeking for dengue ineffective. This systematic review aimed to synthesise the factors influencing healthcare seeking of patients with dengue and form a comprehensive framework. Methods: This review included both qualitative and quantitative studies. Studies were obtained by searching five databases, contacting field experts and performing backward reference searches. The best‐fit meta‐synthesis approach was used during data synthesis, where extracted data were fitted into the social‐ecological model. Sub‐analyses were conducted to identify the commonly reported factors and their level of statistical significance. Results: Twenty studies were selected for meta‐synthesis. Eighteen factors influencing healthcare seeking in dengue were identified and categorised under four domains: individual (11 factors), interpersonal (one factor), organisational (four factors) and community (two factors). The most reported factors were knowledge of dengue, access to healthcare, quality of health service and resource availability. Overall, more barriers to dengue health seeking than facilitators were found. History of dengue infection and having knowledge of dengue were found to be ambiguous as they both facilitated and hindered dengue healthcare seeking. Contrary to common belief, women were less likely to seek help for dengue than men. Conclusions: The factors affecting dengue healthcare‐seeking behaviour are diverse, can be ambiguous and are found across multiple social‐ecological levels. Understanding these complexities is essential for the development of effective interventions to improve dengue healthcare‐seeking behaviour.